Boats for Papa - Bagley, Jessixa (New York : Roaring Brook Press, 2015)
Buckley and his mother cope with the loss of their father/husband by sending small wooden boats, built by Buckley, off into the ocean.
"A Neal Porter Book."
Keywords: Grief -- Juvenile fiction; Mother and child -- Juvenile fiction; Boats and boating -- Juvenile fiction; Grief -- Fiction; Mother and child -- Fiction; Boats and boating -- Fiction; Handicraft -- Fiction; Beavers -- Fiction